Madame de Sade Yukio Mishimy: krew europejskich rycerzy, koronki przedrewolucyjnych dam, japońska scena i bomba atomowa - Tokarski, Błażej (Slavia Occidentalis, 2017)
Madame de Sade, a shingeki play by Yukio Mishima, first published and performed in 1965, still enjoys huge popularity all over the world. In my work, I consider the meaning of the drama and the connections between the Japanese and the European theatre, Marquis de Sade’s philosophy, the French Revolution and the history of Japan. I ask questions about the drama’s popularity and the possibilities for its modern staging.